A strategic analysis of sinking fund bonds - Dunn, Kenneth B.; Spatt, Chester S. (Journal of Financial Economics, 1984)
Unlike most securities, the pricing of sinking fund bonds is influenced by the distribution of ownership, which summarizes the extent to which the market is cornered. The effect of the distribution of ownership on the pricing of sinking fund bonds is examined by an explicit game in which the price obtained for bonds sold can depend upon the size of the investor's position. This framework is used to contrast the valuation of sinking fund bonds with the valuation of amortizing bonds and straight debt. We show that it is generally incorrect to view sinking fund bonds as being equivalent to serial bonds.